Technology and swimming: 3 steps beyond physiology - Berthelot, G.; Hellard, P.; Len, S.; Tafflet, M.; Toussaint, J. F. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
INTRODUCTION: In 2008, the polyurethane made its first appearance in swimming with the use of a new generation of swimsuits. The result was a sudden improvement of performances, repelling the imminent physiological limits (Berthelot et al., 2008). The aim of this study is to quantify the gain provided by the 3 different swimsuits generations introduced in 1999, 2008 and 2009 respectively. METHODS: We collected the best performance of the first 10 world swimmers every year in 34 swimming events from 1990 to 2009. The number of significant values (ANOVA test, p < 0.05) was then summed each year for both sexes. The relative improvement or "gain" between the mean m of the 10 best from one year to the next was computed for all years and all events. RESULTS: Three variation peaks are observed in 2000, 2008 and 2009 corresponding to the year of INTRODUCTION: of each swimsuit. The 1st peak has a higher number of significant variations recorded for women vs. men (13 vs. 9). The 2nd peak presents the highest number of variations, with an equal repartition of significant progressions between men and women (13). The 3rd peak shows a high number of variations for men (9) and fewer variations for women (3). The mean gain values are: 0.74% ±0.26% (2000); 1.16% ±0.48% (2008); 0.68% ±0.55% (2009) for men events and 1.00% ±0.37% (2000); 0.97% ±0.57% (2008); 0.27% ±0.70% (2009) for women events. DISCUSSION: Body shape is one the factors altering drag resistance (Vorontsov and Rumyantsev, 2000). The large impact of the first generation swimsuit on women events suggests that compression of women`s body may have been a major factor reducing hydrodynamical resistance as soon as 2000. This may be the first innovative parameter explaining recent women`s swimming performances. The second generation swimsuit introduced in 2008 provided large gains in both men and women, while the third generation impact is less homogeneous: women showed a lower performance progression, while men experienced a relative improvement. With a period of prohibited swimsuits, we expect a rapid return to physiological thresholds in 2010, which will be partially limited by the allowance of new technology such as starting blocks.